Glioblastoma Stem-Like Cells Are More Susceptible Than Differentiated Cells to Natural Killer Cell Lysis Mediated Through Killer Immunoglobulin-Like Receptors–Human Leukocyte Antigen Ligand Mismatch and Activation Receptor–Ligand Interactions - Haspels, Heleen Neeltje; Rahman, Mohummad Aminur; Joseph, Justin Vareecal; Gras Navarro, Andrea; Chekenya, Martha (Frontiers in Immunology, 2018)
Glioblastoma (GBM) is the most aggressive brain malignancy in adults, where survival is approximately 14.6 months. Novel therapies are urgently needed and immunotherapy has hailed a new dawn for treatment of solid tumors. Natural killer (NK) cells may be amenable therapeutic effectors against heterogeneous GBM, since they also do not require co-stimulation and antigen specificity. However, it is unclear how culture media routinely used in pre-clinical studies affect GBM cell responses to NK mediated cytotoxicity. We hypothesized that the culture medium would affect GBM cell phenotype, proliferation and responses to NK cytotoxicity. We investigated in paired analyses n=6 patient-derived primary GBM cells propagated in stem cell or serum-containing medium for morphology, proliferation, as well as susceptibility to NK cytolysis and related this to expression of surface and intracellular lineage markers, as well as ligands for NK cell activating and inhibitory receptors. We genotyped the GBM cells for human leucocyte antigens (HLA) as well as the killer immunoglobulin receptors (KIR) of the n=6 allogeneic NK cells used as effector cells. Culture in serum-containing medium induced a switch in GBM cell morphology from suspension neuropsheres to adherent epithelial-mesenchymal like phenotypes, which was partially reversible. The differentiated cells diminished expression of nestin, CD133 (prominin-1) and A2B5 putative glioma stem-cell markers, attenuated growth, diminished expression of ligands for activating NK cell receptors, while upregulating class I HLA ligands for NK cell inhibitory receptors. When maintained in serum-containing medium, fewer GBM cells expressed intercellular adhesion molecule-1 (ICAM-1) and were less susceptible to lysis by NK cells expressing αLβ2 integrin receptor (LFA-1), mediated through combination of inhibitory KIR-HLA ligand mismatch and diminished activation receptor-ligand interactions compared to cells maintained in stem cell media. We conclude that development of preclinical immunotherapy strategies against GBM should not use cells propagated in serum-containing media to avoid misinterpretation of potential therapeutic responses.